3−6/5 x=−3

1 answer

To solve the equation \( 3 - \frac{6}{5} x = -3 \), follow these steps:

  1. Isolate the term with \(x\):

    Start by moving the constant term to the right side: \[ -\frac{6}{5} x = -3 - 3 \] \[ -\frac{6}{5} x = -6 \]

  2. Multiply both sides by -1:

    This gives: \[ \frac{6}{5} x = 6 \]

  3. Solve for \(x\):

    Now, multiply both sides by the reciprocal of \(\frac{6}{5}\), which is \(\frac{5}{6}\): \[ x = 6 \times \frac{5}{6} \] \[ x = 5 \]

Thus, the solution is: \[ \boxed{5} \]